Landscapes of the main components, metabolic and microbial signatures, and their correlations during stack “sweating” of Eucommiae Cortex - Wang, Linfeng; Wu, Mengxian; Gu, Bingnan; Wang, Erfeng; Wu, Faliang; Yang, Jiapeng; Guo, Bing; Li, Xingke; Zhang, Pengpai (Frontiers in Microbiology, 2025)
Introduction“Sweating,” a key step in the processing and production of Eucommiae Cortex (EC), which plays a vital role in the formation of the medicinal quality of EC. However, the mechanism of the effect of this traditional treatment of herbs on the quality of herbs is still unclear.MethodsIn this study, high performance liquid chromatography (HPLC), UPLC/MS-based untargeted metabolomics and high-throughput sequencing were applied to investigate the dynamic changes of the main active ingredients, differential metabolites and bacterial communities in the process of “sweating” in EC. The samples were prepared by the traditional stacking “sweating” method, and the samples were collected once a day for five consecutive days.ResultsThe results showed that the contents of the main active constituents, geniposidic acid (GPA), chlorogenic acid (CA), rutin (AU), pinoresinol diglucoside (PD) and total flavonoids (TFS), increased significantly after steaming, followed by a slight decrease. Furthermore, 807 metabolites were identified as crucial factors contributing to the metabolic alterations induced by the “sweating” process. Microbial diversity analysis showed considerable changes in microbiota characteristics, and the main functional microorganisms before and after “sweating” of EC were Gluconobacter, unclassified_c_Gammaproteobacteria, Pseudomonas, Pantoea, Pedobacter, and Parecoccus, which were involved in the five metabolic pathways of other secondary metabolites leading to significant changes in alkaloids, amino acid related compounds, flavonoids, phenylpropanoids and terpenoids.DiscussionThe correlation network established between core bacterial communities, active ingredients, and metabolic pathways elucidates the microbial regulation of EC quality during sweating. These findings provide a scientific foundation for optimizing processing duration and advancing quality control strategies through targeted microbial community management.